Allogeneic CAR T Cells: An Alternative to Overcome Challenges of CAR T Cell Therapy in Glioblastoma - Martínez Bedoya, Darel; Dutoit, Valérie; Migliorini, Denis (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) T cell therapy has emerged as one of the major breakthroughs in cancer immunotherapy in the last decade. Outstanding results in hematological malignancies and encouraging preclinical anti-tumor activity against a wide range of solid tumors have made CAR T cells one of the most promising fields for cancer therapies. CAR T cell therapy is currently being investigated in solid tumors including glioblastoma (GBM), a tumor for which survival has only modestly improved over the past decades. CAR T cells targeting EGFRvIII, Her2 or IL-13R2 have been tested in GBM, but the first clinical trials have shown modest results, potentially due to GBM heterogeneity and to the presence of an immunosuppressive microenvironment. Until now, the use of autologous T cells to manufacture CAR products has been the norm, but this approach has several disadvantages regarding production time, cost, manufacturing delay and dependence on functional fitness of patient T cells, often reduced by the disease or previous therapies. Universal “off-the-shelf”, or allogeneic, CAR T cells is an alternative that can potentially overcome these issues, and allow for multiple modifications and CAR combinations to target multiple tumor antigens and avoid tumor escape. Advances in genome editing tools, especially via CRISPR/Cas9, might allow overcoming the two main limitations of allogeneic CAR T cells product, i.e. graft-versus-host disease and host allorejection. Here, we will discuss how allogeneic CAR T cells could allow for multivalent approaches and alteration of the tumor microenvironment, potentially allowing the development of next generation therapies for the treatment of patients with GBM.